Evaluasi Implementasi Wajib Sertifikasi Kompetensi Individu Msdm Berbasis SK Menteri Ketenagakerjaan RI No. 115/ 2022 - Zuswana, Aries (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to evaluate the implementation of the mandatory competency certification for Human Resource Management (HRM) individuals as stipulated in the Decree of the Minister of Manpower of the Republic of Indonesia No. 115 of 2022. The background for this research is the critical need for competency standardization to enhance the quality and professionalism of HR practitioners, which in turn drives organizational success. A qualitative approach with an evaluative research design was employed to deeply understand the policy's implementation and its impact. The study population includes all stakeholders affected by the policy, such as Professional Certification Bodies (LSP), company leaders, assessors, certified workers (asesi), and professional associations. Purposive sampling was used to select key informants. Data were collected through surveys, in-depth interviews, Focus Group Discussions (FGD), and documentation, and analyzed using the C-I-P-O-I (Context, Input, Process, Output, Impact) systemic thinking approach. The results indicate that the policy's implementation has been effective, with an average index of 3.19. The policy has received strong support from the government and company leaders, resulting in positive impacts on organizational productivity and competitiveness. However, challenges remain, such as the uneven distribution of LSPs and assessors, and the fact that certification has not yet led to a direct increase in compensation for certified practitioners. The study concludes that while the policy is effective, its implementation requires further improvements, particularly in terms of compensation and policy scope.